Dechema corrosion handbook - Kreysa, Gerhard; Schütze, Michael (Dechema, 2008)
Compendium of corrosion data describing the corrosion and chemical resistance of all technically important metallic, non-metallic, inorganic, and organic materials in contact with aggressive media.
Keywords: Corrosion and anti-corrosives -- Handbooks, manuals, etc.; elektronické knihy; electronic books